Caracterização preliminar de elementos a serem considerados para implantação do observatório das trilhas de longo curso do Brasil - Observa Trilhas. - Alves, Thalia Ferreira (My University, 2026)
Observatories add value to data to transform them into information, indicators, and knowledge that support smarter decision-making, contributing to the monitoring and qualification of public policies. Based on these premises, this exploratory research, grounded in documentary analysis and guided by the principles of action research, characterized preliminary elements to be considered in the creation of the Long-distance Trails Observatory of Brazil - ObservaTrilhas (BREGOLIN, RUDZEWICZ, CURZEL, AND ALVES, 2023), a project developed in collaboration with NID ODITT/UCS. To achieve this, the study analyzed the websites of the Chico Mendes Institute for Biodiversity Conservation - ICMBIO (2023), the Ministry of the Environment and Climate Action - MMA (2023), and the Ministry of Tourism - MTUR (2023) as proposers of this public policy, and the Brazilian Trails Network - RBT (2023) as a coordinating entity, in addition to official documents on Long-distance Trails (LDTs) to identify interested audiences and their informational needs. Subsequently, open data sources and visualization tools were explored to enable the initial implementation of this observatory. The results that were found and published on the NID ODITT's public profile on Tableau Public confirmed the feasibility of implementing this observatory. As limitations of the study, it is noted that there was insufficient time to validate the produced visualizations with the actors identified in the research, a situation that will be addressed in future studies. [resumo fornecido pelo autor]
Observatórios agregam valor aos dados para transformá-los em informação, indicadores e conhecimentos que suportam tomadas de decisões mais inteligentes, podendo contribuir para o monitoramento e a qualificação das políticas públicas. Apoiada nessas premissas, esta pesquisa, exploratória, baseada em análise documental e orientada por princípios de uma pesquisa-ação, caracterizou elementos preliminares a serem considerados na criação do Observatório das Trilhas de Longo Curso do Brasil - ObservaTrilhas (REGOLIN, RUDZEWICZ, CURZEL E ALVES, 2023), projeto desenvolvido junto ao NID ODITT/UCS. Para isso, analisou os sites do Instituto Chico Mendes de Conservação da Biodiversidade - ICMBIO (2023), do Ministério do Meio Ambiente e Ação Climática - MMA (2023) e do Ministério do Turismo - MTUR (2023), enquanto propositores dessa política pública, e o site da Rede Brasileira de Trilhas RBT (2023) como articuladora, além de documentos oficiais sobre TLCs para identificar os públicos interessados e suas necessidades informativas. A partir disso, explorou fontes de dados abertos e ferramentas de visualização para viabilizar a implantação inicial desse observatório. Os resultados obtidos e demonstrados no perfil público do NID ODITT no Tableau Public comprovaram a viabilidade da implantação desse observatório. Como limitações do estudo, registra-se o tempo insuficiente para realizar a validação das visualizações produzidas com os atores identificados na pesquisa, situação que será enfrentada em estudos futuros. [resumo fornecido pelo autor]
Keywords: Turismo; Política pública; Trilhas - Brasil